Silica Gel-Supported Poly Phosphoric Acid Catalyzed One-Pot Multi-Componen Synthesis of 2,4,6-Triarylpyridines under Solvent-Free and Microwave Irradiation Conditions - Montazeri, Naser; Pourshamsian, Khalil; Kalantarian, Roya; Mehdi Kia, Mohammad (Asian Journal of Chemistry, 2012)
A simple, green and efficient protocol is developed in which silica gel-supported poly phosphoric acid (PPA-SiO2) is employed as a solid acid catalyst in solvent-free and microwave irradiation conditions for the synthesis of various 2,4,6-triarylpyridines from acetophenones, aryl aldehydes and ammonium acetate. The salient features of the reaction include gool yields, relatively short reaction time and mild reaction conditions. The method is environmentally friendly and does not require solvents.